Reinventing Management - Birkinshaw, Julian (Henry Stewart Talks, 2010)
Why the financial crisis was a failure of management, How management has been corrupted, Why management needs reinventing, Defining a company's Management Model, Bureaucracy versus emergence, Hierarchy versus collective wisdom, Extrinsic versus intrinsic motivation, Alignment versus obliquity, How companies make smarter choices